The Tomb of the Priests of Amun : Burial Assemblages at the National Museum of Denmark Gate of the Priests Series Volume 2 - Sousa, Rogério (Culture and History of the Ancient Near East, 2022)
This book examines the objects of the Danish Lot of antiquities from Bab el-Gasus that are kept at the National Museum of Denmark since 1893 aiming at reconstructing how they were crafted, designed, used and recycled during the 21st Dynasty.